Association of estimated glucose disposal rate with risk of future metabolic dysfunction-associated steatotic liver disease and other chronic liver diseases: a prospective cohort study - Li, Yan; Ye, Xi; Chen, Xiaoyu (Frontiers in Medicine, 2025)
BackgroundThe incidence of insulin resistance, as determined by estimated glucose disposal rate (eGDR), is associated with various morbidities. The relationship between eGDR and chronic liver diseases remains to be explored. This study examined the association between eGDR and the risk of future metabolic dysfunction-associated steatotic liver disease (MASLD), cirrhosis, liver cancer, and liver-related mortality.MethodWe analyzed data from UK Biobank participants with no history of liver diseases. We calculated the eGDR values for each participant and divided them into four quartile groups based on these values. The primary outcome was MASLD, whereas the secondary outcomes included cirrhosis, liver cancer, and liver-related mortality. We estimated hazard ratios (HRs) and 95% confidence intervals (CIs) using Cox proportional hazard regression models. We used restricted cubic splines models to detect potential non-linear relationships.ResultsThis study included data from 290,397 UK Biobank participants who had no history of liver diseases, and the magnetic resonance imaging (MRI)-derived liver proton density fat fraction (PDFF) analysis included 25,810 individuals. Over a median follow-up period of 15.69 years, we identified 3,926 cases of MASLD, 1,553 cases of cirrhosis, 167 cases of liver cancer, and 120 cases of liver-related mortality. After adjusting for multiple variables, higher eGDR levels were significantly associated with a lower risk of MASLD (HR: 0.91, 95% CI: 0.90–0.93), cirrhosis (HR: 0.89, 95% CI: 0.86–0.92), and liver cancer (HR: 0.91, 95% CI: 0.83–1.00). Comparing participants between the lowest and highest quartiles (Q1 and Q4) of eGDR, Q4 had a 47% lower risk of MASLD (HR: 0.53; 95% CI: 0.45–0.63), with similar results for cirrhosis. Moreover, high eGDR levels were associated with a low risk of MASLD based on MRI-derived liver PDFF > 5% (odds ratio: 0.98, 95% CI: 0.97–0.98).ConclusionWe found a significant inverse correlation between eGDR and MASLD, cirrhosis, and liver cancer. Incorporating eGDR into clinical decision-making can improve the long term follow-up of patients with MASLD.